Technical Notes - Effect of Gallium on Resistance to Corrosion of Magnesium Alloys - Benny J. Nelson (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1957)
To obtain information on the effect of gallium upon the corrosion of magnesium alloys, tests were made on the commercial alloy AM52S (Mg-3 pct Al-1 pct Zn-0.2 pct Mn) and experimental